Diseño conceptual de un sistema de tratamiento de aguas residuales para la empresa transportadora escolar Camargo Hermanos S.A. – Tech S.A. (2017)
This project exhibits the development of a system of treatment of wastes water for the company Transportadora Escolar Camargo Hermanos S. A. – TECH S. A. , bearing in mind the analysis of different proposals, the fulfillment of the resolution 0631 of current 2015 with regard to the water vertimiento in superficial bodies and the economic practicality of the project. There decided the characteristics of the generated vertimientos, across analysis physicist - chemist of the wastes water, like the determination of DBO, DQO, pH, solid suspended, presence of fats and oils, phenols and detergents. Later an evaluation was realized to the different water treatment technologies from the established criteria (entire Costs, risk, capacity of removal of impurities, time of the process and adaptation to the politics nationals), the above mentioned study was carried out by means of counterfoils of comparison where the most viable alternative was established for the company. A costs analysis was realized for each of the teams to be used in the proposal, departing from the required minimal parameters and giving major importance to the economic factor because for the operations to be realized it is not necessary to realize expenses raised as materials; the above mentioned analysis was enriched by the analyses of costs of raw material, energy consumption and labor to give like proved the entire costs of the project.